Improving the Wear Resistance and Bending Strength of Knives Used in Centrifugal Beet Cutters - F. Ya. Rudik; S. A. Bredikhin (Сельскохозяйственные машины и технологии, 2019)
The efficiency of sugar production depends largely on the state of beet chips obtained from a centrifugal sugar beet cutter. It is shown that a one-shift operation of defective knives may result in a loss of up to 28-30 percent of sucrose. (Research purpose) To establish quality indicators of beet chips obtained from a centrifugal beet cutter, to improve a design and production technology of knives with increased physical and mechanical characteristics. (Materials and methods) The authors identified the reasons leading to the deterioration of the knife parameters and ensuring the quality of sugar beet cutting. To increase the indicators of wear resistance and bending strength of the cutting edges, the knife design was modified and a new technology of knife manufacturing was offered. The authors theoretically and experimentally proved the feasibility of replacing the manufacturing technology of the cutting edges of knives - from cutting to plastic deformation in die tooling. (Results and discussion) The authors have determined the mechanism and consequences of the wear and breakage of cutting points and the deformation and breakage of cutting edges of sugar beet knives. The technology of edge die stamping with special equipment was offered. The design of tooling for die stamping and machining of knife’s cutting edges was developed and experimentally tested in production conditions. (Conclusions) The authors offered the methods of strengthening cutting edges of knives with die casting, as well as offered solutions to the design problems of knife manufacturing using special high-performance and resource-saving equipment. The main physical and mechanical characteristics of sugar beet knives manufactured according to conventional and improved technologies have been experimentally determined and tested under operating conditions. The authors show the advantages of the cutting edges of sugar beet knives manufactured according to the improved technology; the study has proved an increase in microhardness by 14 percent and an increase in bending strength by 30 percent.